Radiotherapy quality assurance in the TROG 12.01 randomised trial and its impact on loco-regional failure - Corry, June; Moore, Alisha; Kenny, Liz; Wratten, Chris; Fua, Tsien; Lin, Charles; Porceddu, Sandro; Liu, Chen; Ruemelin, Michael; Sharkey, Amy; McDowell, Lachlan; Wilkinson, Dean; et al. (Frontiers in Oncology, 2024)
Introduction There is no consensus as what specifically constitutes Head and neck cancer radiotherapy quality assurance (HNC RT QA). The aims of this study are 1) Describe the RT QA processes used in TROG 12.01 study, 2) review the RT QA processes undertaken for all patients with loco-regional failure (LRF), and 3) provide prospective data to propose a consensus statement regarding the minimal components and optimal timing of HNC RT QA. Materials and methods All patients undergoing RT QA in the original TROG 12.01 study were included in this substudy. All participating sites completed IMRT credentialling and a clinical benchmark case. Real time (pre-treatment) RT QA was performed for the first patient of each treating radiation oncologist, and for 1 in 5 of subsequent patients. Protocol violations were deemed major if they related to contour and/or dose of gross tumour volume (GTV), high dose planning target volume (PTVhd) or critical organs of risk (spinal cord, mandible, brachial plexus). Results Thirty HNROs from 15 institutions accrued 182 patients. 28 clinical benchmark cases, 27 pre-treatment RT QA, and 38 post treatment. Comprehensive RT QA preformed in 65/182, or 36% of treated patients. Major protocol violations were found in: 5/28 benchmark cases,5/27 pre-treatment cases, and 6/38 post-treatment cases. In the 9 patients with LRF - independent review of all 9 LRF cases showed major protocol violations in 4/9. Conclusions Only pre-treatment RT QA can improve patient outcomes. The minimal components of RT QA in HNC are GTVs, PTVhd and critical organs at risk. What constitutes major dosimetric violations needs to be harmonised.